DRD1-DRD5 Expression Profiles in Arthritis Rheumatoid - SADEGHI KOUPAEI, M.T.; AHANGARI, GH.; SAMANGUIEI, SH.; ZOUALI, M.; NAZARI, SH. (Iranian Journal of Child Neurology, 2009)
ObjectivesThe cause of rheumatoid arthritis (RA) as a chronic inflammatory autoimmune disease is still unknown. It appears that both genetic and environmental factors play a role in its pathogenesis. Recent studies reveal that in addition to the CNS, immune cells synthesis neurotransmitters so that these catecholamines can regulate immune functions. The aim of this study is to evaluate the dopamine receptor gene expression profiles on peripheral blood mononuclear cells of rheumatoid arthritis patients in comparison with normal individuals.Material & MethodsIn the present study, we investigated dopamine receptor gene expression in PBMCs of 40 RA patients and 40 healthy individuals using Real Time-PCR.The specificities of the obtained Real time PCR products for the respective dopamine receptors fragments were confirmed by sequenced analysis capillary systemResultsWe found that DRD1-DRD5 types of dopamine receptors genes expression profiles of rheumatoid arthritis patients differ compared to healthy individuals. Moreover, a significant difference of DR2 and DR4 gene expression was seen in rheumatoid arthritis patients.ConclusionThis study showed that some types of dopamine receptors genes expression profiles alter in rheumatoid arthritis patients with comparison to healthy individuals Moreover, this alteration possibly could result in dysfunction of dopaminergic system in immune cells and finally lead to rheumatoid arthritis.